Childhood maltreatment as a risk factor for diabetes: findings from a population-based survey of Canadian adults. (December 2016) - Shields, Margot; Hovdestad, Wendy; Pelletier, Catherine; Dykxhoorn, Jennifer; O'Donnell, Siobhan; Tonmyr, Lil
Abstract Background It is well established that childhood maltreatment (CM) is a risk factor for various mental and substance use disorders. To date, however, little research has focused on the possible long-term physical consequences of CM. Diabetes is a chronic disease, for which an association with CM has been postulated. Methods Based on data from a sample of 21, 878 men and women from the 2012 Canadian Community Health Survey - Mental Health (CCHS - MH), this study examines associations between three types of CM (childhood physical abuse (CPA), childhood sexual abuse (CSA), and childhood exposure to intimate partner violence (CEIPV)) and diabetes in adulthood. Multiple logistic regression models were used to examine associations between CM and diabetes controlling for the effects of socio-demographic characteristics and risk factors for type 2 diabetes. Results When controlling socio-demographic characteristics, diabetes was significantly associated with reports of severe and frequent CPA (OR = 1.8) and severe and frequent CSA (OR = 2.2). A dose–response relationship was observed when co-occurrence of CSA and CPA was considered with the strongest association with diabetes being observed when both severe and frequent CSA and CPA were reported (OR = 2.6). Controlling for type 2 diabetes risk factors attenuated associations particularly for CPA. CEIPV was not significantly associated with having diabetes in adulthood. Conclusion CPA and CSA are risk factors for diabetes. For the most part, associations between CPA and diabetes are mediated via risk factors for type 2 diabetes. Failure to consider severity and frequency of abuse may limit our understanding of the importance of CM as a risk factor for diabetes.